The Development of Interactive Multimedia PowerPoint Geometry Class III in Elementary School - Dila Reski Aryani; Jesi Alexander Alim; Gustimal Witri; Neni Hermita; Muhammad Fendrik (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study has the main purpose to develop a product in the form of interactive multimedia PowerPoint geometry for elementary school students Grade 3 so that the product development is valid and practical. This type of research is development research or research and development. There are three stages that are carried out in developing the model according to the development model, including the development or prototyping stage and the assessment stage. The next Data is done through quantitative and qualitative analysis techniques. Based on the results of interactive multimedia validation developed to obtain results with very valid categories. In addition, you will also get better results. In addition, you will also get the value of the questionnaire practicality by learners obtain results with a very practical category. Based on the description, the product development of this research is interactive geometry multimedia products for elementary school students Grade 3 stated to have met various criteria of validity and practice so that this product can be used by teachers and students in the classroom. In the modern learning process, so that in the learning process can increase the interest and interest of students in learning, even play a role in student psychology.